2001
DOI: 10.1037/1099-9809.7.4.362
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of acculturation and gender to attitudes toward counseling in Italian and Greek American college students.

Abstract: This exploratory study examined attitudes toward professional psychological services and help provider characteristics among 232 self-identified Italian and Greek American college students in 3 Northeast colleges. Regarding general attitudes toward psychological services in the Italian American sample, women had a greater recognition of personal need for help and higher confidence in the ability of mental health professionals to meet these needs than did men. With regard to preferred counselor demographic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…This finding contrasts somewhat with previous research by Dadfar and Friedlander (1982), which suggested that international students in general who lived in the United States longest, reported more positive attitudes towards seeking professional counseling. This contrast suggests perhaps that Caribbean college students are more likely to retain the values of their country of origin and resist the values of the new culture longer than other international student populations that have been researched (Liao et al 2005;Ponterotto et al 2001). This is in line with previous research that suggests that Caribbeans find it more difficult than other groups to assimilate into American culture (Pessar 1995;Stepick 1998).…”
Section: Discussionsupporting
confidence: 74%
“…This finding contrasts somewhat with previous research by Dadfar and Friedlander (1982), which suggested that international students in general who lived in the United States longest, reported more positive attitudes towards seeking professional counseling. This contrast suggests perhaps that Caribbean college students are more likely to retain the values of their country of origin and resist the values of the new culture longer than other international student populations that have been researched (Liao et al 2005;Ponterotto et al 2001). This is in line with previous research that suggests that Caribbeans find it more difficult than other groups to assimilate into American culture (Pessar 1995;Stepick 1998).…”
Section: Discussionsupporting
confidence: 74%
“…Research, particularly amongst Greek and Italian students living in the United States, has shown that women are more favourable about seeking counselling and support for personal need than men. The researchers argued that this is because 'women were more open regarding their personal concerns than men' (Ponterotto et al, 2001). However, for Indians the reason for more men being favourable to counselling than women could be due to the degree of cultural commitments (Price & McNeill, 1992).…”
Section: Discussionmentioning
confidence: 95%
“…As far as we know this is the first study to assess attitudes toward counselling in a purely Greek sample. The only other relevant study has been conducted by Ponterotto et al (2001) using an immigrant GreekAmerican student sample; those researchers reporting that high-acculturated female participants were more open in discussing their psychological concerns that were male participants.…”
Section: Discussionmentioning
confidence: 98%